2012
DOI: 10.1088/0004-637x/754/1/10
|View full text |Cite
|
Sign up to set email alerts
|

FAR-ULTRAVIOLET OBSERVATION OF THE AQUILA RIFT WITHFIMS/SPEAR

Abstract: We present the results of far ultraviolet (FUV) observations of the broad region around the Aquila Rift including the Galactic plane. As compared with various wavelength data sets, dust scattering is found to be the major origin of the diffuse FUV continuum in this region. The FUV intensity clearly correlates with the dust extinction level for E(B − V ) < 0.2, while this correlation disappears for E(B − V ) > 0.2 due to heavy dust extinction combined with the effect of nonuniform interstellar radiation fields.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…On physical scales corresponding to molecular clouds, there can be significant deviations in the relationship between FUV and dust. Observations in Aquila with FIMS/SPEAR (Park et al 2012) found FUV intensity correlates well with dust column for low extinction sightlines, while there is no correlation in regions with higher dust column. Similarly, in the Draco Cloud, Sujatha et al (2010) found substantial variations in the relationship between diffuse FUV intensity and 100 µm intensity using GALEX data.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…On physical scales corresponding to molecular clouds, there can be significant deviations in the relationship between FUV and dust. Observations in Aquila with FIMS/SPEAR (Park et al 2012) found FUV intensity correlates well with dust column for low extinction sightlines, while there is no correlation in regions with higher dust column. Similarly, in the Draco Cloud, Sujatha et al (2010) found substantial variations in the relationship between diffuse FUV intensity and 100 µm intensity using GALEX data.…”
Section: Introductionmentioning
confidence: 87%
“…Ophiuchus, and brights stars, e.g. the spectroscopic binary Spica (at l=316, b=51., Park et al (2012)).…”
Section: Fuv Vs 100 µMmentioning
confidence: 99%
“…Furthermore, the diffuse FUV continuum background radiation probes the dust scattering of starlight (Bowyer 1991;Henry 2002;Seon et al 2011a,b). Hence, a variety of astrophysical targets have been analyzed based on FUV observations, such as supernova remnants (SNRs; Seon et al (2006); Kim et al (2010a,b)), superbubbles (Kim et al 2007;Jo et al 2011Jo et al , 2012, diffuse and molecular clouds, and interstellar dust (Lee et al 2006;Park et al 2009Park et al , 2012Lim et al 2013) .…”
Section: Introductionmentioning
confidence: 99%
“…These limits do not take into account the uncertainty in the dust distribution. Although the bright scattering nebula around HIP 88149 is hidden in the exclusion zone of GALEX, because of the safety restrictions on observing near bright stars, it is prominent in the SPEAR data of Park et al (2012) in the region they call "Ophiuchus". Note that there is no dependence of the modelled or the observed flux on the Galactic latitude.…”
Section: Modelling and Resultsmentioning
confidence: 99%
“…One of the few surveys at low Galactic latitudes was the spectral imaging survey of the SPEAR (Spectroscopy of Plasma Evolution from Astrophysical Radiation: Edelstein et al (2006)) satellite at wavelengths between 900 and 1750 Å. Park et al (2012) combined SPEAR and Galaxy Evolution Explorer (GALEX) data to study the diffuse UV radiation over a 30 square degree region in the vicinity of the Aquila Rift. They deduced that most of the continuum emission was due to dust-scattered light but with contributions from molecular hydrogen fluorescence over part of the field.…”
Section: Introductionmentioning
confidence: 99%